Avaliação da dor em crianças submetidas ao transplante de células-tronco hematopoéticas - Adriana Corrêa Sampaio; Nen Nalú Alves das Mercês; Mauren Teresa Grubisich Mendes Tacla; Márcia Helena de Souza Freire; Letícia Pontes (Universidade Federal do Ceará, 2019)
Objective to evaluate pain in children undergoing transplantation of hematopoietic stem cells.Methods longitudinal and analytical research with children hospitalized for transplant of hematopoietic stem cells with Faces Pain Scale Revised, every four hours from hospital admission to hospital discharge analyzed with relative absolute frequency and chi-square test.Results nine children aged four to nine years old were evaluated, totaling 1,095 ratings in 23.4% were reported with some pain score; of these, 38.9% were in hypo pharynx region; 78.8%, moderate pain. The chi-square showed significance between pain scores weeks post-transplantation and pain existence among the analyzed children.Conclusion although the pain has not affected large proportion of children, moderate and strong pain covered around 80.0% of complaints along the hematopoietic stem cell transplantation process. Thus, it is suggested that the evaluation of pain is one of the signs to be inserted in the protocols of nursing interventions in this context of caring.